KONTRIBUSI KEPEMIMPINAN SAD SASANA DAN MOTIVASI KERJA TERHADAP KINERJA GURU SD DI KABUPATEN BULELENG - Dewi, Putu Yulia Angga; Primayana, Kadek Hengki (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abtract: This study examines Sad Sasana leadership and elementary school teachers' job motivation in Buleleng Regency. Teachers are vital to education, yet low-quality teaching, educational frameworks, and pedagogical practices continue to hinder them. Teachers are crucial to knowledge acquisition and educational progress. Student performance is highly tied to teacher quality. Thus, teachers must have competences matched with national education standards to perform their duties with excellence, resulting in knowledgeable and skilled students. These findings illuminate numerous key characteristics that affect primary teacher performance. In Buleleng Regency, Sad Sasana leadership (X1) directly affects elementary school teachers (Y). The influence of Sad Sasana leadership on teacher performance was 0.806, or 80.6%. Work motivation (X2) significantly affects elementary school teachers' (Y) performance in Buleleng Regency. Work motivation affected teacher performance by 0.583, or 58.3% of the variance.Keywords: Sad Sasana Leadership, Work Motivation, Teacher Performance, Elementary SchoolAbstrak: Studi ini meneliti kepemimpinan Sad Sasana dan motivasi kerja guru sekolah dasar di Kabupaten Buleleng. Guru sangat penting bagi pendidikan, namun pengajaran berkualitas rendah, kerangka kerja pendidikan, dan praktik pedagogis terus menghambat mereka. Guru sangat penting untuk perolehan pengetahuan dan kemajuan pendidikan. Kinerja siswa sangat terkait dengan kualitas guru. Dengan demikian, guru harus memiliki kompetensi yang sesuai dengan standar pendidikan nasional untuk melaksanakan tugasnya dengan sangat baik, sehingga menghasilkan siswa yang berpengetahuan dan terampil. Temuan ini menjelaskan berbagai karakteristik kunci yang memengaruhi kinerja guru sekolah dasar. Di Kabupaten Buleleng, kepemimpinan Sad Sasana (X1) secara langsung memengaruhi guru sekolah dasar (Y). Pengaruh kepemimpinan Sad Sasana terhadap kinerja guru adalah 0,806, atau 80,6%. Motivasi kerja (X2) secara signifikan memengaruhi kinerja guru sekolah dasar (Y) di Kabupaten Buleleng. Motivasi kerja memengaruhi kinerja guru sebesar 0,583, atau 58,3% dari varians.Kata Kunci: Kepemimpinan Sad Sasana, Motivasi Kerja, Kinerja Guru, Sekolah Dasar